2006
DOI: 10.1177/026248930602500203
|View full text |Cite
|
Sign up to set email alerts
|

Key Processing Parameters for Microcellular Molded Polystyrene Material

Abstract: Microcellular injection molding was used as processing method to generate porous samples made of polystyrene material. A promising application for this kind of structures is the use as three dimensional cell culture substrate. The influence of key processing parameters on the morphology of the porous structures was examined. An increase in injection speed and a temperature decrease of the polymer melt decreased pore sizes whereas an increase in the degree of weight reduction increased pore sizes. Polystyrene s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Leicher et al. 20 concluded that the increase of the injection speed and the polymer melt temperature will decrease the pore or cell sizes, whereas the increase in the degree of weight reduction will increase the pore or cell sizes. For microcellular injection molding with gas counter pressure, Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…Leicher et al. 20 concluded that the increase of the injection speed and the polymer melt temperature will decrease the pore or cell sizes, whereas the increase in the degree of weight reduction will increase the pore or cell sizes. For microcellular injection molding with gas counter pressure, Li et al.…”
Section: Introductionmentioning
confidence: 99%
“…Behravesh et al believed that a high pressure drop rate of the polymer melt is required in MIM for a fine bubble morphology with a small bubble size and a high bubble density. They also concluded that shot size is a dominant factor affecting bubble morphology by MIM of a small part having a weight of about 10 g. By using a mold, which is able to produce 10 cylindrical samples with an outer diameter of 12.5 mm, Leicher et al investigated the effect of processing parameters in MIM on bubble morphology. They reported that a higher injection speed, a lower melt temperature or a smaller weight reduction contribute to smaller bubble size and homogeneous bubble morphology.…”
Section: Introductionmentioning
confidence: 99%
“…All of the above studies showed that it is not an easy work to obtain an ideal cell structure in microcellular injection molding, and many efforts have been made in the cell structure control technology. Leicher et al investigated the influence of key processing parameters on the morphology of the microcellular injection‐molded porous structures. It is concluded that the increase of the injection speed and the decrease of the polymer melt temperature will decrease the pore or cell sizes, whereas the increase in the degree of weight reduction will increase the pore or cell sizes.…”
Section: Introductionmentioning
confidence: 99%